Pediatric membranous nephropathy: In the novel antigens era - Huang, Guoping; Liu, Fei; Yu, Ling; Wang, Jingjing; Chen, Junyi; Mao, Jianhua (Frontiers in Immunology, 2022)
Membranous nephropathy (MN) falls within the scope of a glomerular disease. MN exhibits subepithelial immune- complex deposition and capillary wall thickening which could occur in all age groups. In comparison with adult patients with MN, MN in pediatric population has a lower incidence and more secondary factors (e.g., systemic lupus erythematosus, infection, malignancy, or drug toxicity). Two target antigens for the immune complexes, PLA2R (identified in 2009) and THSD7A (in 2014) , found in previous studies and first presented in adult MN, are found in pediatric patients suffering from MN and their antibodies are an effective tool for diagnosis and monitoring in children and adolescents. Several novel antigens have been identified (e.g., EXT1/EXT2, NELL1, Sema3B, PCDH7, HTRA1, and NCAM1) over the past few years. Each of them represents different clinical and pathologic findings. In-depth research should be conducted to gain insights into the outcomes and pathophysiology of the above novel antigen-associated MNs. Targeted treatment opinions for different novel antigen-related MN are under development both in adults and pediatric patients.